Cryptic, sympatric diversity in Tegu lizards of the Tupinambis teguixin Group (Squamata, Sauria, Teiidae) and the description of three new species - Murphy, John C. (2016)
Tegus of the genera Tupinambis and Salvator are the largest Neotropical lizards and the most exploited clade of Neotropical reptiles. For three decades more than 34 million tegu skins were in trade, about 1.02 million per year. The genus Tupinambis is distributed in South America east of the Andes, and currently contains four recognized species, three of which are found only in Brazil. However, the type species of the genus, T. teguixin, is known from Bolivia, Brazil, Colombia, Ecuador, French Guyana, Guyana, Peru, Suriname, Trinidad and Tobago, and Venezuela (including the Isla de Margarita). Here we present molecular and morphological evidence that this species is genetically divergent across its range and identify four distinct clades some of which are sympatric. The occurrence of cryptic sympatric species undoubtedly exacerbated the nomenclatural problems of the past. We discuss the species supported by molecular and morphological evidence and increase the number of species in the genus Tupinambis to seven. The four members of the T. teguixin group continue to be confused with Salvator merianae, despite having a distinctly different morphology and reproductive mode. All members of the genus Tupinambis are CITES Appendix II. Yet, they continue to be heavily exploited, under studied, and confused in the minds of the public, conservationists, and scientists.